Post-stroke inflammation and the potential efficacy of novel stem cell therapies: focus on amnion epithelial cells - Broughton, Brad R.; Lim, Rebecca; Arumugam, Thiruma V.; Drummond, Grant R.; Wallace, Euan M.; Sobey, Christopher G. (Frontiers in Cellular Neuroscience, 2013)
Ischemic stroke is a debilitating disease for which there are currently no effective treatments besides the clot-buster, tissue plasminogen activator, which is administered to less than 10 % of patients due to a limited (4.5 h) time window of efficacy. Thus, there is an urgent need for novel therapies that can prevent or reverse the effects of stroke-induced brain injury. Recent encouraging reports have revealed that stem cells derived from human tissue, including embryonic, induced pluripotent, neural, and mesenchymal cells, can rescue injured brain tissue and improve functional recovery in experimental models of stroke. However, there are potentially major limitations to each of these types of stem cells that may ultimately prevent or restrict their use as viable mainstream treatment options for stroke patients. Conversely, stem cells derived from the placenta, such as human amnion epithelial cells (hAECs), appear to have several important advantages over other stem cell lineages, in particular their non-tumorigenic and non-immunogenic characteristics. Surprisingly, so far hAECs have received little attention as a potential stroke therapy. This brief review will firstly describe the inflammatory response and immune cell involvement following stroke, and then consider the potential for hAECs to improve stroke outcome given their unique characteristics. These actions of hAECs may involve a reduction of local inflammation and modulation of the immune response, promotion of neural recovery, differentiation into neural tissue, re-innervation of lost connections, and secretion of necessary cytokines, growth factors, hormones and/or neurotransmitters to restore cellular function.